Biological Distribution in Patients of Boron Agent 4-Borono-L-Phenylalanine for Boron Neutron Capture Therapy - ZHU Xia-yang; LIU Kai; SHAO Yu-jun; JIN Cong-jun; ZHAO Chun-yuan; CHONG Yi-zheng; GUO Zhi-bin; SUN Qi; LIU Zhi-bo; LIU Tong; ZHANG Zi-zhu (He huaxue yu fangshe huaxue, 2023)
Boron neutron capture therapy(BNCT) is a binary targeted radiation therapy in which neutron does not directly provide tumor dose. The dose produced by the 10B(n, α)7Li capture reaction will be deposited in tumor cells by using targeted 10B agents. Therefore, understanding the biological distribution of 10B agents in the blood, tumor and normal tissue is essential for BNCT. 4-borono-L-phenylalanine(BPA) is the mainly used 10B agent in BNCT clinical trials worldwide. In order to support and facilitate the preparation of BPA-based BNCT clinical trials, information on the structure, physicochemical properties, cellular uptake mechanisms and human biological distribution of BPA are summarized in this paper.